1969
DOI: 10.2307/1933886
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of C‐14 in Products of Photosynthesis and Its Relationship to Phytoplankton Composition and Rate of Photosynthesis

Abstract: Relationships among the phytoplankton standing crop, rate of photosynthesis, and the distribution of C—14 in primary products of photosynthesis were investigated in western Lake Erie from July to August 1965. Sixty species of phytoplankton were noted during the study, but only four species, Coscinodiscus sp, Ceratium hirundinella (O.F.M.) Schrank, Aphanizomenon flos—aquae (L) Ralfs, and Microcystis aeruginosa Kutz accounted for over 98% of the total cell volume. Cell volumes ranged from 10 to 282 mm3 liter—1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1973
1973
2000
2000

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Ensuite on evapore B sec I'extrait, on le reprend B l'eau distillbe puis on le passe successivement sur deux &sines: Amberlite IR 120 et Amberlite IRA 410 (AKAGAWA et al, 1972). Comme l'a fait WATT (1966) on a prbfbd ce procbdb celui de l'extraction chimique di€ferentielle (OLIVE et al, 1969…”
Section: Introductionunclassified
“…Ensuite on evapore B sec I'extrait, on le reprend B l'eau distillbe puis on le passe successivement sur deux &sines: Amberlite IR 120 et Amberlite IRA 410 (AKAGAWA et al, 1972). Comme l'a fait WATT (1966) on a prbfbd ce procbdb celui de l'extraction chimique di€ferentielle (OLIVE et al, 1969…”
Section: Introductionunclassified
“…Several researchers have indicated that the biochemical composition of algae is variable and dependent on the cellular growth stage. In exponentially growing populations, the main biochemical "product" is protein (Olive et £j_., 1969). Darley (1977) The amount of cellular carbohydrate and lipid is greater in senescent cells than in actively-growing cells (Badour and Gergis, 1965;Handa, 1969;Opute, 1974b;Conover, 1975).…”
Section: Literature Reviewmentioning
confidence: 99%